Copper molybdate nanoparticles for electrochemical water splitting application. (11th February 2021) - Keerthana, S.P.; Rani, B. Jansi; Yuvakkumar, R.; Ravi, G.; Shivatharsiny, Yohi; Babu, E. Sunil; Almoallim, Hesham S.; Alharbi, Sulaiman Ali; Velauthapillai, Dhayalan
Abstract: Two different phases of copper molybdate nanoparticles such as Cu3 Mo2 O9 and Cu6 Mo5 O18 were synthesized through schematic hydrothermal treatment. The obtained product morphology was explored by using surfactants like sodium lauryl sulfate (SDS) and polyvinylpyrrolidone (PVP). The structural, optical, vibrational and morphological properties were confirmed employing standard characterization techniques. Rectangular nanoflakes of the obtained product were confirmed by employing Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) studies. Selected area electron diffraction (SAED) pattern confirms obtained product crystalline nature. The better morphology controlled sample gives higher 227 mA/g current density at 10 mV/s and small 184 V overpotential. Long duration stability over 16 h was exhibited by Cu6 Mo5 O18 electrode. Hence, Cu6 Mo5 O18 electrode shows better electrochemical activity with stunning low overpotential. It would be suggested that PVP surfactant is quite optimum to produce efficient Cu6 Mo5 O18 catalysts for electrochemical water splitting applications. Highlights: An excellent electrochemical water oxidation was demonstrated. Cu6 Mo5 O18 exhibited outstanding 227 mA/g current density. Cu6 Mo5 O18 exhibited very low 184 mV overpotential.